Influence of in vitro pigmenting of esthetic orthodontic ligatures on smile attractiveness - Camila Ferraz; Marcelo Castellucci; Márcio Sobral (Dental Press Editora, 2012)
OBJECTIVE: To evaluate the perception of dental students and orthodontists on the degree of influence that pigmented esthetic elastic ligatures have on smile attractiveness, by judging clinical photographs. METHODS: Sixteen clinical facial photographs of the smile and 16 close up images of the smile of a single patient wearing monocrystalline porcelain orthodontic brackets, Teflon coated NiTi wire brackets and esthetic elastic ligatures of five different commercial brands were distributed into eight groups, G1 to G8 (Morelli®, Ortho Tecnology™, TP Orthodontics™, Unitek/3M™clear, Unitek/3M™ obscure, American Orthodontics™ clear, American Orthodontics™ pearl and American Orthodontics™ metallic pearl). Twenty ligatures were used in each group, totaling 160 ligatures. Half of them were used in their natural state, and the other half after in vitro pigmentation. All the photographs were judged by 40 evaluators, 20 orthodontists and 20 dental students. RESULTS: For orthodontists, American™ pearl (G7) ligatures were those that least influenced the degree of attractiveness of the smile in the two types of photographs used. For the dental students, in the facial photographs of the smile, ligatures with the best performance were Morelli® (G1), American™ clear (G6) and American™ pearl (G7) and in the close up photographs of the smile, American™ pearl, metallic pearl and clear (G7, G8 and G6). CONCLUSIONS: For both orthodontists and dental students, pigmentation of the elastic ligatures had a negative influence on the degree of attractiveness of smiles in the two types of clinical photographs evaluated. OBJETIVO: avaliar, através de fotografias clínicas, entre estudantes de Odontologia e ortodontistas, o grau de influência que ligaduras elásticas estéticas pigmentadas exercem sobre a atratividade do sorriso. MÉTODOS: foram utilizadas 16 fotografias clínicas faciais do sorriso e 16 de sorriso aproximado de um único paciente portando braquetes ortodônticos de porcelana monocristalina, fio de NiTi teflonado e ligaduras elásticas estéticas de cinco marcas comerciais diferentes, distribuídas em oito grupos, G1 a G8 (Morelli, Ortho Technology, TP Orthodontics, 3M/Unitek clear, 3M/Unitek obscure, American Orthodontics clear, American Orthodontics pearl e American Orthodontics metalic pearl). Foram utilizadas 20 ligaduras de cada grupo, totalizando 160 ligaduras. Metade delas foi utilizada em estado natural e a outra metade após pigmentação in vitro. Todas as fotografias foram julgadas por 40 avaliadores, sendo 20 ortodontistas e 20 estudantes de Odontologia. RESULTADOS: para ortodontistas, as ligaduras American Orthodontics pearl (G7) foram as que menos influenciaram o grau de atratividade do sorriso nos dois tipos de fotografias utilizadas. Para os estudantes de Odontologia, nas fotografias faciais do sorriso, as que obtiveram o melhor desempenho foram Morelli (G1), American Orthodontics clear (G6) e American Orthodontics pearl (G7) e, nas fotografias de sorriso aproximado, American Orthodontics pearl, metalic pearl e clear (G7, G8 e G6, respectivamente). CONCLUSÕES: tanto para ortodontistas quanto para estudantes de Odontologia, a pigmentação das ligaduras elásticas influenciou de forma negativa o grau de atratividade dos sorrisos nos dois tipos de fotografias clínicas avaliadas.